Analysis of Factors Hypertension in Online-Based Transportation Driver in Kediri City - Arif Mustofa; Nurwijayanti Nurwijayanti; Rahmania Ambarika (Journal for Quality in Public Health, 2020)
One of the actions that can be taken to prevent hypertension is to develop knowledge about the level of vulnerability on several factors that influence it. It is expected that with enough knowledge to feel the level of vulnerability can increase awareness of hypertension. The purpose of this study was to determine the effect of the level of vulnerability on factors of sleep quality, stress, and eating patterns on hypertension in online-based transportation drivers in Kediri City. The research design used is quantitative research using the "cross sectional" approach. The sampling technique used was simple random sampling with a sample of 164 respondents. The data analysis technique uses a logistic regression multivariate test. The results showed that the sleep quality variable a significance value of 0,000 <(α = 0.05), meaning that H0 is rejected and H1 is accepted which means that there is an influence between sleep quality on the incidence of hypertension. In the stress variable it is known a significance value of 0.004 <(α = 0.05), meaning that H0 is rejected and H1 is accepted, which means that there is an influence between stress levels on the incidence of hypertension. In the variable eating patterns it is known a significance value of 0,000 <(α = 0.05), meaning that H0 is rejected and H1 is accepted which means that there is an influence between eating patterns on the incidence of hypertension. Knowledge of the level of vulnerability to the causes of hypertension can increase one's awareness of the dangers of the disease so that they can take early precautions and protect themselves from the threat of the disease.